Chiral 2-C-methylene glycosides and carbohydrate-derived pyrano[2,3-b][1]benzopyrans: synthesis via InCl3 catalyzed stereoselective ferrier rearrangement of 2-C-acetoxymethyl glycal derivatives - Ghosh, R.; Chakraborty, A.; Maiti, D. K.; Puranik, Vedavati G. (Tetrahedron Letters, 2005)
2-C-Acetoxymethyl glycal derivatives react with aliphatic alcohols in the presence of InCl3 (30 mol %) to furnish the corresponding 2-C-methylene glycosides in excellent yields and with exclusive alpha-selectivity except for the methyl 2-C-methylene glycosides, which are formed in similar to 2:1 anomeric ratio in favour of the alpha-anomer. The reaction of 2-C-acetoxyglycals with phenols, however, produces the corresponding chiral carbohydrate-derived pyranobenzopyran derivatives via initial Ferrier rearrangement followed by tandem cyclization in excellent yields and moderate to high stereoselectivities in favour of the corresponding 10a-R-pyrano[2,3-b][1]benzopyran derivatives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 2-C-methylene glycoside; InCl3; pyranobenzopyran; Stereoselective